Analisis Usability Aplikasi Investasi Digital Menggunakan Metode Heuristic Evaluation dan System Usability Scale - Yesi Sriyeni (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
The world of digital investment is currently growing rapidly and is starting to get a lot of attention from the people of Indonesia, even though it was down during the Covid-19 pandemic, the world of digital investment still has its own charm. The emergence of several digital investment application platforms such as Bibit is a solution to introduce the investment world to the general public that investing is easy and can be started with small capital. In line with the investment startup goal of Bibit.id, which has a target to invite the public to invest, a mobile-based Bibit application was launched with a simple user interface and easily understood by the general public. This study aims to analyze the usability of the Seedling application using the heuristic evaluation approach as a measuring tool for functionality with 10 (ten) test indicators from Nielsen and the system usability scale (SUS) approach method to test usability from the end user side. The test questionnaire was given to 30 users and 3 evaluators. From this study, the overall test results found no serious functionality problems in the seed application as evidenced by the average severity rating of 1.4 which was rounded on a scale of 1, namely cosmetics problem, which means that there is no need to fix problems in seed application. From testing using SUS based on end users, the results obtained from the interpretation of the SUS score of 83.75 with an application acceptance rate in the